A Markov model for ranking cricket teams playing one day international matches - Anuthrika, T.; Arivalzahan, S.; Tharshan, R. (Vingnanam Journal of Science, 2019)
Main purpose of ranking teams in One Day International (ODI) Cricket matches is to identify challenging teams of each team. In the sports science literature, various statistical procedures have been proposed by different researchers to rank teams. International Cricket Council (ICC) is using a ranking system as the standard practice. However, it does not work well to realize some head-to head match results. This paper provides a stochastic Markov chain model to rank teams. A comprehensive analysis on head-to-head match prediction for each cricket team is given based on steady-state probabilities. Performance of the proposed model is investigated with ICC ODI rankings. It is shown that the proposed model outperforms to predict results of head-to-head ODI Cricket matches.
Keywords: Stochastic Process; Markov Model; Steady-State Probability; One Day International Cricket ranking